2003
DOI: 10.1118/1.1568591
|View full text |Cite
|
Sign up to set email alerts
|

Verification of absolute ionization chamber dosimetry in a proton beam using carbon activation measurements

Abstract: Reference ionization chamber dosimetry implemented in a clinical proton beam and based on the ICRU 59 recommendations has been verified with an independent carbon activation method. The 12C(p,pn)11C nuclear reaction was used to measure the beam fluence and entrance dose. A method to transfer from the entrance dose to the dose at the ion chamber calibration position has been developed. Measurements performed in a monochromatic 200 MeV beam show that the ratio of absolute doses measured using the carbon activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…An alternative method that overcomes this problem is the use of activation measurements that can determine the fluence of a broad beam directly if the cross‐section for the formation of the isotope being quantified is known with sufficient accuracy. This method was demonstrated by Nichiporov using the cross‐section for the formation of 11 C in a scintillating polystyrene sample. Aside from this problem, the fluence‐based approach has the intrinsic disadvantage that the uncertainty on the stopping power enters directly in the overall uncertainty of the dose determination.…”
Section: Detectors For Measurements Of Absorbed Dose In Reference Conmentioning
confidence: 99%
“…An alternative method that overcomes this problem is the use of activation measurements that can determine the fluence of a broad beam directly if the cross‐section for the formation of the isotope being quantified is known with sufficient accuracy. This method was demonstrated by Nichiporov using the cross‐section for the formation of 11 C in a scintillating polystyrene sample. Aside from this problem, the fluence‐based approach has the intrinsic disadvantage that the uncertainty on the stopping power enters directly in the overall uncertainty of the dose determination.…”
Section: Detectors For Measurements Of Absorbed Dose In Reference Conmentioning
confidence: 99%
“…Sample activation measurements. Larsson and Sarby (1987) and Nichiporov (2003) demonstrated that accurate dosimetry of a proton beam can also be achieved using a sample activation measurement. To this end, a sample with a known number, N, of 12 C atoms is irradiated at the phantom surface.…”
Section: Faraday Cup Measurementsmentioning
confidence: 99%
“…To this end, a sample with a known number, N, of 12 C atoms is irradiated at the phantom surface. After an irradiation of time interval τ , the proton fluence can be derived from a measurement of the 11 C activity, A 0 , using 4π βγ -coincidence counting and known values of the 12 C(p, pn) 11 C reaction cross section, σ , and the decay constant, λ, of 11 C using the expression (Nichiporov 2003)…”
Section: Faraday Cup Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, 11 C is produced in the irradiated tissue as a by-product of the radiotherapy with protons or heavy ions and its spatial distribution can be determined with a positron emission tomography (PET) camera during or after the treatment [32]. On the other hand, dosimetry of proton fields with activated graphite foils has been proposed as an alternative approach to ionization chamber based dosimetry [28]. Such applications in medical physics require an accurate knowledge of the nat C(p,x) 11 C cross section in the therapeutic energy range (proton energies up to 250 MeV) and suitable uncertainties for the accuracy required for radiotherapy.…”
Section: Introductionmentioning
confidence: 99%